Limits of formal regulation: how informal norms and criminogenic values affect managers’ readiness to corrupt - Hermann, Dieter; Pohlmann, Markus; Klinkhammer, Julian (Organizational crime, 2023)
The study tests hypotheses regarding the influence of norms and values on the readiness to corrupt. The data are 250 online interviews with managers. Analytically, we distinguish between organizational and individual corruption as well as between informal and formal norms. Organizational corruption focuses on the expected benefits for the organization and the relevance of informal organizational norms. On the other hand, individual corruption emphasizes the benefits for the actor and the relevance of formal norms, whereas informal norms of organizational usefulness recede into the background. The study shows that the readiness for organizational corruption is quantitatively larger than the readiness for individual corruption. The rejection of conformity, tradition, benevolence, universalism, and self-direction, the preference for achievement, power, and hedonism, as well as the acceptance of informal norms in a company are the most important conditions for the readiness to corrupt. These results support the voluntaristic theory of crime and substantiate institutional theories of organizational sociology.
Gesehen am 11.05.2023